1996
DOI: 10.1007/bf03011676
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous anaesthesia: new drugs, new concepts, and clinical applications

Abstract: During the course of the past decade, three distinct developments have resulted in the widespread clinical application of intravenous anaesthesia: (a) the world-wide introduction of propofol and alfentanil in the late 1980s; (b) enhanced understanding of the pharmacodynamics and pharmacokinetics of iv anaesthetic drugs (e.g., context-sensitive half-times); (c) commercial availability of programmable ,syringe infusion pumps for intravenous infusion techniques While many of the advantages and some of the limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Large increases, an order of magnitude larger than seen with propofol or etomidate shown here, would indicate serious, unacceptable accumulation and dominating redistribution of the drug. [2][3][4] During stable anaesthesia, established using a closed-loop system, other measures to assess depth of anaesthesia could be tested and cardiorespiratory and other variables could be measured easily. We found that paw withdrawal during propofol anaesthesia was less pronounced than the response during etomidate anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large increases, an order of magnitude larger than seen with propofol or etomidate shown here, would indicate serious, unacceptable accumulation and dominating redistribution of the drug. [2][3][4] During stable anaesthesia, established using a closed-loop system, other measures to assess depth of anaesthesia could be tested and cardiorespiratory and other variables could be measured easily. We found that paw withdrawal during propofol anaesthesia was less pronounced than the response during etomidate anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Performance was also assessed quantitatively in each individual experiment. For this purpose the standard deviation (SD) of the BSR distribution around the BSR target during the 10-50-min time interval (2400 s) was determined according to equation (3). The first 10 min were excluded because of the initial fluctuations, and the last 10 min because in some experiments the paw pressure stimulus influenced BSR stability.…”
Section: Continuous Infusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Propofol was one of the first agents to directly challenge thiopental as the standard induction agent (Miller, 1996).…”
Section: Problem Of Reducing Costsmentioning
confidence: 99%
“…fentanyl, and midazolam. [ 15 16 17 ] Further surgery/adjustment is done based on the correction achieved. The purpose of this study was to determine if this allows us to optimize the number of rectus muscles operated and achieve good motor alignment.…”
mentioning
confidence: 99%